Workshop PkM Analisis Pola Data dengan Python untuk Data Driven Decision Making - Irawan Wingdes; Susanti Susanti (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of digital technology has increased the need for data analysis skills in the workplace and entrepreneurship. However, the introduction of business data analysis using computer programming is still limited at the Vocational High School (VHS) level. This community service activity aims to improve students' understanding and provide additional training on the use of data for decision-making at SMK Negeri 3 Pontianak. The community service activity was conducted in the form of a workshop involving 62 students. This workshop included material delivery, data analysis practice using Python, and pre- and post-test evaluations to measure participants' understanding of data-driven decision-making. The evaluation results showed an increase in the average score of participants from 2.48 in the pre-test to 4.04 in the post-test, a 62.9% increase. These results indicate that the workshop effectively improved students' understanding of business data pattern analysis and the use of data as a basis for decision-making in the workplace and entrepreneurship.